An Antioxidant Enzyme Therapeutic for COVID‐19. Issue 43 (13th September 2020) - Qin, Meng; Cao, Zheng; Wen, Jing; Yu, Qingsong; Liu, Chaoyong; Wang, Fang; Zhang, Jianjun; Yang, Fengmei; Li, Yanyan; Fishbein, Gregory; Yan, Sen; Xu, Bin; et al.
Abstract: The COVID‐19 pandemic has taken a significant toll on people worldwide, and there are currently no specific antivirus drugs or vaccines. Herein it is a therapeutic based on catalase, an antioxidant enzyme that can effectively breakdown hydrogen peroxide and minimize the downstream reactive oxygen species, which are excessively produced resulting from the infection and inflammatory process, is reported. Catalase assists to regulate production of cytokines, protect oxidative injury, and repress replication of SARS‐CoV‐2, as demonstrated in human leukocytes and alveolar epithelial cells, and rhesus macaques, without noticeable toxicity. Such a therapeutic can be readily manufactured at low cost as a potential treatment for COVID‐19. Abstract : A catalase‐based therapeutic is developed for COVID‐19, which eliminates excessively produced reactive oxygen species, prevents oxidative injury, regulates production of cytokines, and represses replication of SARS‐CoV‐2 in ex vivo cell studies and rhesus macaques, providing a low‐cost yet effective therapeutic for the pandemic and hyperinflammation in general.